Prognostic Significance of Albumin-Globulin Ratio in Urachal Carcinoma - Chen, Hengxin; Wu, Menghai; Chen, Minfeng (Urologia internationalis, 2025)
Although albumin-globulin ratio (AGR) has been used in the prognostic assessment of multiple solid malignancies, so far no research has confirmed the prognostic significance of AGR as a biomarker for urachal carcinoma. We analyzed the relationship between AGR and prognosis in urachal carcinoma, aiming to identify a promising prognostic biomarker for urachal carcinoma. We reviewed the clinical data of 25 patients diagnosed with urachal carcinoma in the Xiangya Hospital, Central South University, from January 2008 to October 2021. The best cut-off value of preoperative AGR was determined according to the receiver operator characteristic curve. The Kaplan-Meier curve was used to analyze the effect of preoperative AGR on the overall survival (OS) and relapse-free survival (RFS) of patients. Cox proportional hazards model was used to analyze prognostic factors including preoperative AGR. The best cut-off value of preoperative AGR in urachal carcinoma patients is 1.45. Low preoperative AGR is significantly associated with worse OS and RFS. Univariate analysis and multivariate analysis indicated that low preoperative AGR is an independent and reliable factor to predict poor prognosis, OS, and RFS in urachal carcinoma patients. Urachal carcinoma patients with low preoperative AGR have worse prognosis, and preoperative AGR is a valuable prognostic indicator for urachal carcinoma research.